2019
DOI: 10.1007/s40199-019-00246-7
|View full text |Cite
|
Sign up to set email alerts
|

Using the transtheoretical model’s stages of change to predict medication adherence in patients with type 2 diabetes mellitus in a primary health care setting

Abstract: Background Qatar is currently experiencing a worrying increase in the prevalence of diabetes mellitus (DM). One of the most common reasons for uncontrolled DM is non-adherence to medications. The socio-behavioral intervention has proven effective in some chronic illnesses. Objectives To assess the stages of change (SOC) and medication adherence scores of type 2 diabetes mellitus (T2DM) patients visiting primary healthcare institutions in Qatar, and to evaluate the cause and effect relationship between SOC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
2
2
1
1
Order By: Relevance
“…The SOC model may explain how these changes occur over time and could be the reason for increased self-care adherence among individuals having diabetes for more than 6 years compared to those having diabetes for 6 months-3 years. A study conducted by Arafat et al (2019) reported an association between diabetes duration, SOC, and medication adherence among people with T2D, results that are consistent with the current study findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The SOC model may explain how these changes occur over time and could be the reason for increased self-care adherence among individuals having diabetes for more than 6 years compared to those having diabetes for 6 months-3 years. A study conducted by Arafat et al (2019) reported an association between diabetes duration, SOC, and medication adherence among people with T2D, results that are consistent with the current study findings.…”
Section: Discussionsupporting
confidence: 92%
“…This may be the reason individuals with diabetes for more than 3-6 years do not differ in their self-care adherence from those with diabetes for 6 months-3 years and over 6 years. However, this finding is contrasted by a study (Arafat et al, 2019) that reported a positive correlation between disease duration and self-care adherence.…”
Section: Discussioncontrasting
confidence: 75%
“…O monitoramento de usuários do sistema de saúde pode ser uma estratégia que contribui para mudanças oportunas e que facilita o estabelecimento de metas de colaboração direta com os pacientes ao se desenvolver planos de cuidado centrado nas necessidades do paciente 1 . Portanto, acredita-se que essa estratégia seja promissora, para aumentar a capacidade de autogerenciamento de doenças crônicas não transmissíveis, como o diabetes mellitus e a hipertensão arterial, sendo de suma importância na melhoria da qualidade de vida relacionada à saúde, na adesão a práticas de exercício e na adesão medicamentosa 2 .…”
Section: Introductionunclassified
“…The TTM produces favourable health outcomes by encouraging participants to move forward through the SOC. [ 21 , 22 ] Pharmacists currently use the SOC approach to assist participants with smoking cessation [ 23 , 24 ], but as far as can be determined from the literature, they have not yet applied the model to other health behaviours.…”
Section: Introductionmentioning
confidence: 99%